2021
DOI: 10.1523/jneurosci.2799-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the Neural Correlates of Consciousness and Task Relevance in Face Perception Using Simultaneous EEG-fMRI

Abstract: Current theories of visual consciousness disagree about whether it emerges during early stages of processing in sensory brain regions or later when a widespread frontoparietal network becomes involved. Moreover, disentangling conscious perception from task-related postperceptual processes (e.g., report) and integrating results across different neuroscientific methods remain ongoing challenges. The present study addressed these problems using simultaneous EEG-fMRI and a specific inattentional blindness paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 103 publications
3
42
0
Order By: Relevance
“…The VAN has been suggested to index the ERP differences between supraliminal and subliminal conditions [43]. Here, we show that complex and meaningful stimuli like human faces are associated with a large VAN when they are clearly visible to the participants and gain access to awareness, compared to when they are rendered subliminal and hence not consciously processed, consistent with previous studies also using face stimuli [22,44,45].…”
Section: Van Does Not Require Spatial Attention Focus But Can Be Enha...supporting
confidence: 91%
“…The VAN has been suggested to index the ERP differences between supraliminal and subliminal conditions [43]. Here, we show that complex and meaningful stimuli like human faces are associated with a large VAN when they are clearly visible to the participants and gain access to awareness, compared to when they are rendered subliminal and hence not consciously processed, consistent with previous studies also using face stimuli [22,44,45].…”
Section: Van Does Not Require Spatial Attention Focus But Can Be Enha...supporting
confidence: 91%
“…In addition to being important for future research, consideration of multivariate methods is also critical in assessing previous no-report studies. Although a wide variety of prior results have shown the importance of no-report paradigms for consciousness studies, virtually all of them fail to use more nuanced decoding measures like the ones described here, 24,[26][27][28][29][30]32,34,62 but see Kapoor et al 35 and Dwarakanath et al 62 In fact, in a prior study from our laboratories, we found that one particular candidate signature of conscious processing, the P3b, completely disappeared in a no-report paradigm like the one described here, which goes against key predictions made by the global neuronal workspace theory. 30 This previous result is perfectly consistent with our univariate measures, which found that overall activity levels in the frontal lobe completely disappeared in the no-report conditions (Figures 3 and 4).…”
Section: The Importance Of Multivariate Methodsmentioning
confidence: 93%
“…We do not explicitly try to model this very slow cortical dynamic activity here. Our model is agnostic as to whether the entire late distributed activity pattern represents conscious access alone, or whether some of the activity could prepare a conscious report, or other post-access conscious processing (Cohen et al 2020;Dellert et al 2021;Pitts et al 2018Pitts et al , 2012Pitts et al , 2014Schlossmacher et al 2020;Sergent et al 2021). Simulation of activity patterns during cognitive tasks in connectome-based dynamical models is in its infancy, and the types of tasks that have been simulated are particularly simple (Froudist-Walsh et al 2021a;Mejias and Wang 2022).…”
Section: Network Cellular Synaptic Mechanisms Of Conscious Accessmentioning
confidence: 99%